Financial assistance: the new approach - Pinnock, Steven (Centre for Law and Society, 2026)
Several jurisdictions, including South Africa, regulate the granting by a company of financial assistance for the acquisition of its own shares. Some permit financial assistance unconditionally, others regulate financial assistance according to strict conditions and others prohibit it subject to minor exceptions. After statutorily being introduced into company legislation in the early part of the 20th Century, there are still questions as to why this law is still so prominent, and whether such regulation or prohibition is a necessary component of company law in the modern commercial environment, or more specifically the South African commercial environment where the prohibition has been an impediment to Black Economic Empowerment (BEE) deals. The prohibition against financial assistance has been criticised by numerous academics and practitioners, and many jurisdictions have over time amended their laws dealing with financial assistance to make it less burdensome and restrictive.1 South Africa finally relaxed its financial assistance prohibition contained in section 38 of the Companies Acf- in 2007 when the Corporate Laws Amendment Act3 came into operation with the introduction of the US modelled solvency and liquidity test.